Health loss and economic burden of asthma in China: a qualitative review based on existing literature - Peng Zhang; Jiaxin Xu; Baichuan Xu; Yiyin Zhang; Yang Xie (Archives of Public Health)
Abstract Background Asthma is a significant public health issue that cannot be ignored in China and around the world, bringing a huge social burden. Objectives To evaluate the disease burden of asthma in China, including health loss and cost of illness, and identify its influencing factors. Methods A systematic literature review and qualitative descriptive analysis were conducted, Literature was accessed through PubMed, EMBASE, Web of Science, CNKI, Wangfang Data, and VIP databases, with a cutoff date of April 3, 2024. The analysis focused on two main aspects: health loss burden, measured by disability-adjusted life years (DALYs), including years of life lost (YLLs) and years lived with disability (YLDs); and economic burden, assessed through direct and indirect costs. The risk of bias in economic studies was assessed using an 11-item methodological checklist for cost of illness, while cross-sectional studies were evaluated using the Agency for Healthcare Research and Quality’s recommendation rating tool. Results The analysis included 50 studies, with eight focused on health loss and 42 on economic burden. The health loss studies showed a 51% decrease in asthma's age-standardized DALYs rate over 30 years, from 209.24 to 102.81 per 100,000 person-years. The health loss burden is influenced by factors such as high BMI, smoking, and occupational exposure. Economic burden studies reported annual direct costs from $348 to $1187 per capita, indirect costs from $7 to $1195, and hospitalization costs from $177 to $1547, influenced by frequency and severity of acute exacerbation, comorbidities, and treatment adherence. Quality assessment revealed moderate overall quality, with gaps in sensitivity analyses and cost data transparency. Conclusion The health loss burden of asthma in China has significantly decreased from 1990 to 2019, with males experiencing a higher burden. However, regional disparities in the economic burden persist, highlighting the need for improved management and adherence to standardized treatment protocols to address these disparities.